2020
DOI: 10.1017/s1751731120000634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic position of Hungarian Grey among European cattle and identification of breed-specific markers

Abstract: Hungarian Grey is an indigenous cattle breed that is one of the national symbols of Hungary. However, genetic description of the Hungarian Grey cattle has not yet been conducted based on whole-genome screening. Using the GeneSeek high-density Bovine SNP (single nucleotide polymorphism) 150 K BeadChip, we sampled the genome of 36 Hungarian Grey, 12 Maremmana, 13 Hungarian Fleckvieh and 5 Holstein-Friesian cattle for population studies and used data of 139 other cattle from an additional dataset created on Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Multidimensional scaling analysis on IBS allele-sharing values revealed a clear separation between Maremmana and the other Podolian-derived Italian breeds along the first dimension (C1; Figure 2 ). This clustering trend was confirmed by the neighbor joining (NJ) tree of individuals, which revealed two major clades that coincide with Maremmana and the rest of the Podolian-derived populations ( Supplementary Figure S1 ), in agreement with previous studies ( Senczuk et al, 2020 ; Zsolnai et al, 2020 ). It is also noteworthy that, both MDS and NJ tree revealed additional substructure of Maremmana suggesting the presence of individuals from several sub-populations with different allele frequencies.…”
Section: Resultssupporting
confidence: 90%
“…Multidimensional scaling analysis on IBS allele-sharing values revealed a clear separation between Maremmana and the other Podolian-derived Italian breeds along the first dimension (C1; Figure 2 ). This clustering trend was confirmed by the neighbor joining (NJ) tree of individuals, which revealed two major clades that coincide with Maremmana and the rest of the Podolian-derived populations ( Supplementary Figure S1 ), in agreement with previous studies ( Senczuk et al, 2020 ; Zsolnai et al, 2020 ). It is also noteworthy that, both MDS and NJ tree revealed additional substructure of Maremmana suggesting the presence of individuals from several sub-populations with different allele frequencies.…”
Section: Resultssupporting
confidence: 90%
“…The estimates of H E and H O were not dissimilar, 0.261 and 0.274 respectively, which suggests that there are no major recent events pushing heterozygosity in either direction. On a smaller sample size (N = 12), H E were estimated at 0.369 and 0.381 from 150k SNP data [39]. More recently, from 48 k SNP data and sample size N = 25, estimates of H E = 0.319 and H O = 0.338 were obtained [40].…”
Section: Genetic Diversity Of Maremmana Cattlementioning
confidence: 99%
“…Moreover, our results contrast with those of the MDS plot reported by Zsolnai et al . [ 46 ] that showed that Hungarian Grey clustered independently from the other European Podolian cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Balkan breeds, the Podolsko Serbian, Croatian Podolian and Hungarian Grey breeds are the most differentiated, which confirms the genetic differentiation of the Hungarian Grey breed with respect to other Podolian and non-Podolian European taurine found by Zsolnai et al . [ 46 ]. The observed distinctness of these Balkan breeds (including the Romanian Grey), might be the result of a strong genetic drift, as suggested by the low values obtained for the genetic diversity indices and effective population size (Table 1 ) and (see Additional file 4 : Figure S2) and the long branches in the TREEMIX graphs (Fig.…”
Section: Discussionmentioning
confidence: 99%